Factors affecting employee satisfaction at PT. Angkasa Pura Support - Sabri Sabri; Mia Ayu Gusti (Enrichment : Journal of Management, 2023)
This researcher aims to determine employee job satisfaction at PT. Angkasa Pura Support is influenced by practical HRM like work environment, compensation, job security, supervisor support, coworker support and career development. All employees of PT. Angkasa Pura Support, totaling 13,648 people, constitutes the research population using the purposive sampling method and obtained a sample of 219 people. The survey method was used to collect data by distributing questionnaires online. With the Multiple Linear Regression Analysis technique with the help of SPSS software, the results show that the work environment, supervisor support, coworker support, and career development have an important role in increasing employee job satisfaction at PT Angkasa Pura Support, while compensation and job security do not have an important role in To increase employee job satisfaction, this must be addressed because one of the factors that makes a person satisfied in completing his duties and responsibilities is compensation, so this can be implemented by creating a rational competition and compensation system.